SOCIEDAD Y PERSONA ADULTA MAYOR. SIGNIFICADOS PARA PERCIBIR BIENESTAR SUBJETIVO - Riverón Hernández, Karina; Jocik Hung, Georgina (Universidad de Costa Rica, 2013)
The main objective of this article is present the meanings that the Bayamo elderly adult uses to construct his perception of subjective well-being in interaction with society. Also, it addresses the definitions of subjective well-being that elderly people have as well as the necessary elements to perceived wellness in your life. The meanings are identified in two directions of society towards the elderly (social support, understanding, respect) and the elderly to society (social contribution).